Bioactive inorganic particles‐based biomaterials for skin tissue engineering. Issue 5 (17th March 2022) - Ma, Jingge; Wu, Chengtie
Abstract: The challenge for treatment of severe cutaneous wound poses an urgent clinical need for the development of biomaterials to promote skin regeneration. In the past few decades, introduction of inorganic components into material system has become a promising strategy for improving performances of biomaterials in the process of tissue repair. In this review, we provide a current overview of the development of bioactive inorganic particles‐based biomaterials used for skin tissue engineering. We highlight the three stages in the evolution of the bioactive inorganic biomaterials applied to wound management, including single inorganic materials, inorganic/organic composite materials, and inorganic particles‐based cell‐encapsulated living systems. At every stage, the primary types of bioactive inorganic biomaterials are described, followed by citation of the related representative studies completed in recent years. Then we offer a brief exposition of typical approaches to construct the composite material systems with incorporation of inorganic components for wound healing. Finally, the conclusions and future directions are suggested for the development of novel bioactive inorganic particles‐based biomaterials in the field of skin regeneration. Abstract : The inorganic biomaterials for wound healing have aroused widespread concern in the field of tissue engineering. The three main forms of application of inorganic particles for skin repair are summarized based on the complexity of material system. The representative types of inorganic biomaterials and fabrication technology of wound dressings are presented.